ヒカリ ディスク ヲ モチイタ ショウワ キチ アイスランド チジキ キョウヤク テン カンソク データベース システム ノ カイハツ - 山岸, 久雄; ヤマギシ, ヒサオ; Yamagishi, Hisao (1990)
P(論文) 南極昭和基地及びその地磁気共役点であるアイスランドにて, 超高層物理現象の長期モニタリングが1983年より本格的に開始され, 今後少なくとも1太陽活動周期(11年)にわたる観測が計画されている。現在, 膨大なデジタルデータが蓄積されつつある。これらのデータを最近発達した光ディスクを記録媒体として効率的に管理し, また任意期間の任意観測データを表示することができるデータベースシステムを作成した。本報告ではシステムの基本設計, 機能, 操作法についてまとめた。 Long-term monitoring of upper-atmosphere-physics phenomena has been carried out at Syowa Station-Iceland geomagnetically conjugate pair since 1983,and this project will further continue to cover at least 1 solar-activity cycle of 11 years. A great amount of digital data has been accumulated and waiting for efficient data management. Hence a data base system is developed with a help of the recent progress of optical-disk technique. The function of the system comprises (1) management of data storage, (2) data display, and (3) unloading of specified data. This report describes the basic concept of system design, system function, and operation. departmental bulletin paper